Hobbes and the Law of Nature - Zagorin, Perez (Book collections on Project MUSE., 2009)
Thomas Hobbes remains one of the most challenging and controversial of early modern philosophers, and debates persist about the interpretation of many of his ideas, particularly his views about natural law and natural right. In this book, Perez Zagorin argues that these two concepts are the twin foundations of the entire structure of Hobbes's moral and political thought. Zagorin clears up numerous misconceptions about Hobbes and his relation to earlier natural law thinkers, in particular Hugo Grotius, and he reasserts the often overlooked role of the Hobbesian law of nature as a moral standard from which even sovereign power is not immune. Because Hobbes is commonly thought to be primarily a theorist of sovereignty, political absolutism, and unitary state power, the significance of his moral philosophy is often underestimated and widely assumed to depend entirely on individual self-interest. Zagorin reveals Hobbes's originality as a moral philosopher and his importance as a thinker who subverted and transformed the idea of natural law. --From publisher's description.